Perbaikan Kelarutan Albendazol Melalui Pembentukan Kristal Multikomponen dengan Asam Malat: Improvement of Albendazole Solubility Through Multicomponent Crystal Formation with Malic Acid - Alatas, Fikri; Abdul Azizsidiq, Fahmi; Hartyana Sutarna, Titta; Ratih, Hestyari; Nurono Soewandhi, Sundani (Universitas Tadulako, 2020)
An effort to improve the solubility of albendazole (ABZ), an anthelmintic drug has been successfully carried out through the formation of multicomponent crystal with dl-malic acid (MAL). Construction of phase solubility curve of ABZ in MAL solution and crystal morphological observations after recrystallization in the acetone-ethanol (9:1) mixture were performed for initial prediction of multicomponent crystal formation. ABZ-MAL multicomponent crystal was prepared by wet grinding or also known as solvent-drop grinding (SDG) with acetone-ethanol (9:1) mixture as a solvent followed by characterization of the multicomponent crystal formation by powder X-ray diffraction and Fourier transform infrared (FTIR) methods. The solubility of ABZ-MAL multicomponent crystal was tested in water at ambient temperature and in pH 1.2, 4.5 and 6.8 of buffered solutions at 37Â°C. The phase solubility curve of the ABZ in the MAL solution showed type Bs. The ABZ-MAL mixture has a different crystalline morphology than pure ABZ and MAL after recrystallization in the acetone-ethanol mixture (9:1). The powder X-ray diffraction pattern and the FTIR spectrum of ABZ-MAL from SDG different from intact ABZ and MAL powder X-ray diffraction patterns and these results can indicate the ABZ-MAL multicomponent crystal formation. The ABZ-MAL multicomponent crystal has better solubility than pure ABZ in all media used. These results can be concluded that ABZ-MAL multicomponent crystal can be prepared by solvent-drop grinding method with acetone-ethanol (9:1) mixture as a solvent and can increase the solubility of albendazole.